Financial barriers in accessing medical care for peripheral artery disease are associated with delay of presentation and adverse health status outcomes in the United States. (February 2020) - Jelani, Qurat-ul-ain; Jhamnani, Sunny; Spatz, Erica S; Spertus, John; Smolderen, Kim G; Wang, Jingyan; Desai, Nihar R; Jones, Philip; Gosch, Kensey; Shah, Samit; Attaran, Robert; Mena-Hurtado, Carlos
Patient-reported difficulties in affording health care and their association with health status outcomes in peripheral artery disease (PAD) have never been studied. We sought to determine whether financial barriers affected PAD symptoms at presentation, treatment patterns, and patient-reported health status in the year following presentation. A total of 797 United States (US) patients with PAD were identified from the Patient-centered Outcomes Related to TReatment Practices in Peripheral Arterial Disease: Investigating Trajectories (PORTRAIT) study, a prospective, multicenter registry of patients presenting to vascular specialty clinics with PAD. Financial barriers were defined as a composite of no insurance and underinsurance. Disease-specific health status was measured by Peripheral Artery Questionnaire (PAQ) and general health-related quality of life was measured by EuroQol 5 (EQ5D) dimensions at presentation and at 3, 6, and 12 months of follow-up. Among 797 US patients, 21% ( n = 165) of patients reported financial barriers. Patients with financial barriers presented at an earlier age (64 ± 9.5 vs 70 ± 9.4 years), with longer duration of symptoms (59% vs 49%) (all p ⩽ 0.05), were more depressed and had higher levels of perceived stress and anxiety. After multivariable adjustment, health status was worse at presentation in patients with financial barriers (PAQ: –7.0 [–10.7, –3.4]; p < 0.001 and EQ5D: –9.2 [–12.74, –5.8]; p < 0.001) as well as through 12 months of follow-up (PAQ: –8.4 [–13.0, –3.8]; p < 0.001 and EQ5D: –9.7 [–13.2, –6.2]; p < 0.001). In conclusion, financial barriers are associated with later presentation as well as poorer health status at presentation and at 12 months.ClinicalTrials.gov Identifier: NCT01419080